ANALISIS EFISIENSI PRODUKTIVITAS ALAT BERAT DUMP TRUCK, ASPHALT FINISHER, TANDEM ROLLER, DAN PNEUMATIC TYRED ROLLER PADA PEKERJAAN JALAN ( Study Kasus : Pembangunan Jalan Patimoa-Arawawo) - Ferdinandus Antonius So; Yono Putra; Yosef Norbertus Tembu Muda (SIARTEK - Jurnal Teknik Sipil dan Arsitektur, 2021)
The productivity and working time of heavy equipment is one of the most important factors in determining the success of a construction project to reduce work delays which cause wasted costs. This research aims to determine the value of productivity and working time of heavy equipment on the Patimoa-Arawawo road construction project with a length of 2000 m. The heavy equipment that will be analyzed in this research is the Dump Truck, Asphalt Finisher, Tandem Roller, and Pneumatic tread roller. This research uses a method for calculating the actual production capacity of heavy equipment, namely calculating heavy equipment speed, heavy equipment cycle time, equipment efficiency factors, and the production capacity of the Asphalt Mixing Plant (AMP) used according to what happens in the field. The results of the analysis of heavy equipment productivity and working time obtained from this research are Dump trucks for HRS Base work productivity of 3.71 m3/day and working time 5 days, Dump trucks for Aggregate work productivity of 7.56 m3/hour and working time 1 day, Asphalt finisher productivity is 33.32 m3/hour and working time is 2 days, Tandem roller productivity is 23.32m3/hour and working time is 2 days, Pneumatic Tyred roller productivity is 18.29 m3/hour and working time is 2 days, and Asphalt Mixing Plant (AMP) production is 6.40 m³/hour and the working time is 6 days.